Assessment of Current Therapy and Advanced Management Methods for Acetylsalicylic Acid–Associated Gastropathy in Individuals with Cardiovascular Disease - Anvarovich, Djumayev Akbar (American Journal of Bioscience and Clinical Integrity, 2025)
The aim of this review is to summarize and critically analyze contemporary evidence (2019–2025) regarding the incidence, mechanisms of development, clinical features, and preventive measures of gastropathy in cardiology patients receiving acetylsalicylic acid (ASA). The review includes an evaluation of meta-analyses, systematic reviews, major randomized controlled trials, and data from clinical registries. Particular attention is given to approaches to gastroprotection, the impact of Helicobacter pylori infection, the significance of different ASA formulations, and aspects of combined antithrombotic therapy. The article provides practical conclusions and recommendations relevant to clinical practice.